Sistem Penyimpanan Energi Baterai (BESS) untuk Optimasi Beban Puncak: Solusi Cerdas Efisiensi Energi Industri - Sofyan Sofyan; Ng Rong Wee; Umar Muhammad; Herra Ramdani Hakim (Politeknik Bosowa, 2025)
Battery Energy Storage Systems (BESS) have emerged as an innovative solution to enhance energy efficiency in commercial and industrial sectors, particularly through the implementation of peak shaving methods. This technology enables energy storage during periods of low demand and its utilization during peak demand, thereby reducing the load on the power grid. This study explores the integration of BESS in managing electrical loads to lower peak energy consumption while improving operational efficiency and power system stability. By utilizing daily load profile data and BESS parameters, a system is developed to regulate charging and discharging processes to achieve optimal energy balance. Simulation results indicate that BESS implementation can reduce peak loads by up to 50%, distribute energy more evenly throughout the day, and enhance the reliability and efficiency of the power grid. This technology also offers environmental benefits by reducing dependence on fossil fuel-based power plants and supporting the transition toward a more sustainable energy system.